2013
DOI: 10.3390/molecules181012180
|View full text |Cite
|
Sign up to set email alerts
|

Lepidotrichilins A and B, New Protolimonoids with Cytotoxic Activity from Trichilia Lepidota (Meliaceae)

Abstract: Two novel protolimonoids, named lepidotrichilins A (1) and B (2), four known protolimonoids, 21,23-epoxy-7α-21α-dihydroxyapotirucalla-14,24-dien-3-one (3), 21,23-epoxy-7α-21β-dihydroxyapotiru-calla-14,24-dien-3-one (4), dysorone D (5), deoxyflindissone (6), and the two steroids β-sitosterol (7) and stigmasterol (8) ) and the protolimonoid deoxy-flindissone (6; IC 50 9.3 µgmL −1 ) exhibited significant cytotoxic activity against the MOLT-4 and U937 leukemic cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…48,50 Dereplication analysis of a number of semipurified fractions obtained from the VLC purification of the medium polarity fraction S6). 51,52 Similarly, and even though the dereplication analysis of fraction 2J (Figure S23) S8). 45,53 Similarly, the monohydroxylated xanthone 4 could be detected in fraction 2K (Figures S30 and S31, Table S9).…”
Section: Resultsmentioning
confidence: 81%
“…48,50 Dereplication analysis of a number of semipurified fractions obtained from the VLC purification of the medium polarity fraction S6). 51,52 Similarly, and even though the dereplication analysis of fraction 2J (Figure S23) S8). 45,53 Similarly, the monohydroxylated xanthone 4 could be detected in fraction 2K (Figures S30 and S31, Table S9).…”
Section: Resultsmentioning
confidence: 81%
“…In recent studies, the anticancer properties have been found in some plant extracts and their isolated compounds developed by the researchers. Amongst them is X. granatum , a well-known mangrove plant, a rich source of bioactive compounds, such as protolimonoids (apotirucallanes) [ 57 , 58 ], gedunin [ 16 ], xylogranatumines A–G [ 53 ], protoxylocarpins F–H [ 25 ], and so on, which showed anticancer activity. Besides, protolimonoids exhibited a wide range of bioactivities, including insecticidal [ 59 ], and CDC25B (M-phase inducer phosphatase 2) inhibitory properties [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The protolimonids 6 isolated from this plant were more toxic (IC50 9.3 mg/mL) compared to both strains tested. As for the extracts, the hexanic (IC50 62.5mg/mL) exhibited the most significant cytotoxic activity against both strains (Terra et al, 2013). It is important to note that protolimonids are proven to be toxic to tumor cells.…”
Section: Trichilia Lepidota Martmentioning
confidence: 99%